Trigeminal Neuralgia - Yadav, Yad Ram (Asian J Neurosurg, 2017)
Trigeminal neuralgia (TN) is a sudden, severe, brief, stabbing, and recurrent pain within one or more branches of the trigeminal nerve. Type 1 as intermittent and Type 2 as constant pain represent distinct clinical, pathological, and prognostic entities. Although multiple mechanism involving peripheral pathologies at root (compression or traction), and dysfunctions of brain stem, basal ganglion, and cortical pain modulatory mechanisms could have role, neurovascular conflict is the most accepted theory. Diagnosis is essentially clinically; magnetic resonance imaging is useful to rule out secondary causes, detect pathological changes in affected root and neurovascular compression (NVC). Carbamazepine is the drug of choice; oxcarbazepine, baclofen, lamotrigine, phenytoin, and topiramate are also useful. Multidrug regimens and multidisciplinary approaches are useful in selected patients. Microvascular decompression is surgical treatment of choice in TN resistant to medical management. Patients with significant medical comorbidities, without NVC and multiple sclerosis are generally recommended to undergo gamma knife radiosurgery, percutaneous balloon compression, glycerol rhizotomy, and radiofrequency thermocoagulation procedures. Partial sensory root sectioning is indicated in negative vessel explorations during surgery and large intraneural vein. Endoscopic technique can be used alone for vascular decompression or as an adjuvant to microscope. It allows better visualization of vascular conflict and entire root from pons to ganglion including ventral aspect. The effectiveness and completeness of decompression can be assessed and new vascular conflicts that may be missed by microscope can be identified. It requires less brain retraction.